(untitled) (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. The absolute dominance of the isolated muscle presentation as the first and last word in muscular anatomy leaves the current generation of therapists unlikely to think any other way (Myers, 2009). Hypothesis: functional relationships could be found between pelvic floor, diaphragm, and trunk muscles in men with prostate cancer. Research aim. The aim of the study was to evaluate functional associations between pelvic floor, diaphragm, and trunk muscles among men with prostate cancer. Research methods. The study included 81 male volunteers diagnosed with prostate cancer with measurements conducted one day before radical prostatectomy. Pelvic floor muscle strength and endurance were measured using “Peritron 9300” device, the strength of diaphragm – with “MicroRPM”, the strength of transversus abdominis muscle – with “Stabilizer”. Trunk muscles were tested using tests for static postural endurance of abdominal and back muscles. Associations were estimated using Pearson’s correlation coefficient (r). Research results. Analysis of functional indicators of muscles demonstrated high linear associations between strength of pelvic floor and diaphragm (r = 0.79), between strength of diaphragm and exhalation muscles (r = 0.78), and between static endurance of abdominal and back muscles (r = 0.72). We determined moderate correlations between endurance of pelvic floor and strength of transversus abdominis muscle (r = 0.59), between strength of transversus abdominis and static endurance of abdominal muscles (r = 0.69), between strength of diaphragm and static endurance of abdominal (r = 0.56) and back muscles (r = 0.51), between the strength of exhalation muscles and static endurance of abdominal muscles (r = 0.57) and strength of pelvic floor (r = 0.65), between strength of pelvic floor and static endurance of back muscles (r = 0.50). Low correlations were found between strength of pelvic floor and transversus abdominis (r = 0.31) and static endurance of abdominal muscles (r = 0.44), between endurance of pelvic floor and exhalation muscles (r = 0.37), and finally between transversus abdominis and static strength of back muscles (r = 0.39). All correlations were statistically significant (p < 0.01). Discussion and conclusions. The findings showed positive associations among different functional indicators of muscles: strength of pelvic floor correlates with endurance of pelvic floor muscles, static abdominal and back muscles, strength of diaphragm, and transversus abdominis muscles. The results of this study confirm that functional associations between pelvic floor, diaphragm, and trunk muscles exist. Keywords: abdominal muscles, static postural endurance, respiration, core stability.